Implementation of smart-passive dampers combined with double concave friction pendulum devices to retrofit an existing highway viaduct exploiting the seismic early warning information. (1st August 2016) - Nestovito, Gianluca; Occhiuzzi, Antonio
Highlights: The assessment of existing viaducts built without the concepts of seismic engineering is mandatory for the in force standards. The combined use of semi-active dampers, friction pendulum devices and seismic early warning system, is investigated for an existing viaduct. The linking between dampers and early warning system is realized using a control algorithm for a calibration of devices. The effectiveness and robustness of the investigated strategy is compared with a consolidate anti-seismic technology. The results attested that the approach proposed results in a more robust seismic behavior of the structure. Abstract: The seismic events occurred in recent years have highlighted the extreme vulnerability of a large part of existing Italian highway infrastructure. The principal skeleton of Italian highway network was built during the mid-century, where the knowledge of seismic engineering was still limited. Also, the old age of structures with the need of seismic assessment, is forcing highway stakeholders to give an answer to a strategic query: should thousands of highway bridges be destroyed and re-built with in force regulations, or do they just need a retrofit? The objective of this work is to reply concretely to that issue, investigating the combined use of a dissipative smart-passive control strategy and an innovative isolation system to protect seismically excited structures. It is based on the use of seismic early warning information (SEWI) to optimally calibrate variable dampers for a higher reduction of the structural response. In particular, the adoption of dissipative magnetorheological (MR) dampers calibrated according to the forecasted value of the seismic peak ground acceleration, and a new adaptive control algorithm, are herein proposed. Moreover, to reduce the influence of support devices in the global viaduct behavior, a prototype of double concave friction pendulum (DCFP), with a very low value of friction coefficient, is implemented. The effectiveness and robustness of the DCFPs system with smart-passive MR dampers driven by the SEWI, are demonstrated with reference to an existing Italian highway viaduct for the first time. The results of non-linear time history analysis using seismic registrations of natural events are then compared with a consolidate passive technique characterized by lead rubber bearings (LRB), applied to the same structure. The control technique results were promising for the ease of implementation for structures, effectiveness, even compared with a widespread passive system and robustness, given an estimate of the incoming earthquake by a seismic early warning system.